ASSESSMENT OF KNOWLEDGE, ATTITUDES, AND PRACTICES IN INFECTION PREVENTION AND CONTROL AMONG HEALTH-CARE WORKERS AT THE GOVERNMENT TEACHING HOSPITAL, VISAKHAPATNAM - sasapu, swapna; P, Kamala; P, Sateesh kumar (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objectives: The purpose of this questionnaire-based study is to assess frontline healthcare professionals’ knowledge and awareness of infection prevention and control policies and procedures. Methods: This is a cross-sectional study in which the knowledge and practices of the study group (Doctors, Nurses, and Laboratory Technicians) were assessed using an electronic Google form questionnaire. Data were collected and statistically analyzed. Results: There were 67 doctors, 18 laboratory technicians, and 35 nurses among the 120 responses analyzed. The majority of respondents (67%) were females and majority (50%) were between the ages of 21 and 30 years, with a mean age of 28. Among the respondents, 67% participated in training programs and 28% completed a certified course in infection prevention control. The majority (95%) were aware of all the standard precautions. Knowledge levels on hand washing, respiratory hygiene, and biomedical waste management were 85%, 77%, and 62% respectively. In comparison to knowledge, their attitudes toward infection control were lower (81%). In this study, only 70% of participants followed WHO guidelines for hand washing. More than 74% are familiar with the single-handed scoop technique for recapping needles. Only 50% know correct sequence of donning and doffing of PPE. Conclusion: The study participants have gaps in their knowledge and application of infection control. It would be beneficial for all HCW to receive formal and refresher training periodically.